PENGOMPOSAN LIMBAH ORGANIK UNTUK MEWUJUDKAN ZERO WASTE MANAGEMENT DI RW VII DUKUH MENANGGAL KOTA SURABAYA - Dwi Haryanta; Tatuk Tojibatus Sa’adah; Indarwati Indarwati (LP2M Universitas Ibrahimy, 2023)
The 'zero waste' movement in waste management has not been consistently implemented to build a sustainable cycle. However, residents of RW VII Dukuh Menanggal have adopted 'zero waste management' practices, including waste bank activities and composting of leaf waste in jumbo biopores. Community service initiatives aim to promote appropriate technology for leaf waste composting using the d'Wijaya method, increase the capacity for processing organic matter into compost, and enhance residents' skills in using compost for vegetable cultivation. These activities encompass socialization, counseling, and assistance in implementing the composting method. Planning, implementation, and evaluation involve the community directly, fostering a sense of ownership of the program. These community service activities have led to increased insight, knowledge, and skills among residents regarding composting of leaf waste and tree branch waste using the d'Wijaya method, as well as using compost for vegetable growth. The implementation of the 'zero waste management' concept in RW VII has resulted in a reduction of waste transported to temporary disposal sites (TDS) by more than 50%. This program could serve as an initial step towards establishing an independent composting facility within the RW area in Surabaya.